2022
DOI: 10.3389/fpubh.2022.884701
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Epitope Protein as a Tool of Serological Diagnostic Development for HTLV-1 and HTLV-2 Infections

Abstract: A multi-epitope protein expressed in a prokaryotic system, including epitopes of Env, Gag, and Tax proteins of both HTLV-1 and HTLV-2 was characterized for HTLV-1/2 serological screening. This tool can contribute to support the implementation of public policies to reduce HTLV-1/2 transmission in Brazil, the country with the highest absolute numbers of HTLV-1/2 infected individuals. The chimeric protein was tested in EIA using serum/plasma of HTLV-infected individuals and non-infected ones from four Brazilian s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Additionally, the combination of epitopes derived from several distinct viral proteins with low reactivity among flaviviruses is clearly advantageous when compared to the use of full-length proteins. The successful use of multi-epitope chimeric proteins has been increasingly documented in the literature, and includes chimeric proteins for the diagnosis of Trypanosoma cruzi [ 47 ], Burkholderia pseudomallei [ 48 ], Human T-cell lymphotropic virus [ 49 , 50 ], Brucella [ 51 ], Leishmania braziliensis [ 52 ], among others. These publications also demonstrate the reliability and feasibility of a multi-epitope recombinant approach for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the combination of epitopes derived from several distinct viral proteins with low reactivity among flaviviruses is clearly advantageous when compared to the use of full-length proteins. The successful use of multi-epitope chimeric proteins has been increasingly documented in the literature, and includes chimeric proteins for the diagnosis of Trypanosoma cruzi [ 47 ], Burkholderia pseudomallei [ 48 ], Human T-cell lymphotropic virus [ 49 , 50 ], Brucella [ 51 ], Leishmania braziliensis [ 52 ], among others. These publications also demonstrate the reliability and feasibility of a multi-epitope recombinant approach for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The approach used to select different epitopes in different proteins of the infectious agent has also been successfully attempted using other selection methods for HTLV as a novel opportunity for diagnosis. 60 …”
Section: Discussionmentioning
confidence: 99%
“…The approach used to select different epitopes in different proteins of the infectious agent has also been successfully attempted using other selection methods for HTLV as a novel opportunity for diagnosis. 60 In the present study, the phage display method showed the importance of using CPAF for diagnosis, but this protein has already been used in a murine model as a sufficient immunizer against C. muridarum, inducing protective CD4 + T lymphocytedependent immunity and IFN-γ production. 61 The description of clones G1, H5, C6 and H7 and the conserved structure of CPAF indicate the presence of four epitopes that are also conserved, a finding that can be tested for the production of future vaccines with universal use for human primates and other animals infected by Chlamydia species.…”
mentioning
confidence: 82%
“…coli BL21(λDE3) cells ELISA 22 rubella-positive serum samples/11 rubella-negative serum samples Sensitivity: 100% Specificity: 90.91% [ 114 ]/Brazil Human HTLV-1 and HTLV-2/human T-lymphotropic viruses 1 and 2 HTLV-1/HTLV-2 E . coli Rosetta-gami 2(DE3) cells ELISA 162 HTLV-positive serum samples/297 serum samples from healthy individuals/92 serum samples from non-HTLV disease HTLV-1 and HTLV-2 samples Sensitivity: 82.41 to 92.36% Specificity: 90.09% to 95.19% HTLV-1 samples Sensitivity: 99.19% Specificity: 92.55% HTLV-2 samples Sensitivity: 57.14% Specificity: 94.61% [ 115 ]/Brazil Human chikungunya/chikungunya virus MULTREC Binary system insect cell/baculovirus ELISA 161 chikungunya-positive serum samples/22 serum samples from healthy individuals/312 serum sample from non-chikungunya diseases Sensitivity: 86.36% Specificity: 100% [ 116 ]/Brazil “–”: information not provided by the study …”
Section: Rmps Applied In Disease Diagnosismentioning
confidence: 99%
“…In addition to the bioinformatics tools mentioned below, there are specific E. coli strains developed to mitigate those potential issues. In this regard, an E. coli Rosetta-derived lineage was used to express RMPs designed for T. cruzi, W. bancrofti, and human HTLV detection [ 10 , 115 , 126 ]. This lineage harbors extra copies of genes encoding rare tRNAs, including for AUA, AGG, AGA, CUA, CCC, and GGA codons [ 142 ].…”
Section: Escherichia Coli : the Platform Of Choice For Rmp P...mentioning
confidence: 99%